2022
DOI: 10.1093/schbul/sbac070
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, Revascularization, and Cardioprotective Pharmacotherapy After Acute Coronary Syndrome in Patients With Severe Mental Illness: A Systematic Review and Meta-analysis

Abstract: Background and Hypothesis People with severe mental illness (SMI) may experience excess mortality and inequitable treatment following acute coronary syndrome (ACS). However, cardioprotective pharmacotherapy and SMI diagnoses other than schizophrenia are rarely examined in previous reviews. We hypothesized that SMI including bipolar disorder (BD) is associated with increased post-ACS mortality, decreased revascularization, and cardioprotective medication receipt relative to those without SMI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…The excess risk of cardiovascular death in people with diabetes and SMI might also reflect more severe cardiovascular events and potential differences in cardiac care both in the acute phase and subsequently. Previous research from our group and others found that, among people with an MI and compared to those without mental illness, patients with an SMI were less likely to receive coronary revascularisation procedures, less likely to survive 30-days post-MI and more likely to experience a further vascular event (36,37). The adverse cardiac and metabolic side effects of some antipsychotic medications may also play a role in the poorer outcomes (38,39).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The excess risk of cardiovascular death in people with diabetes and SMI might also reflect more severe cardiovascular events and potential differences in cardiac care both in the acute phase and subsequently. Previous research from our group and others found that, among people with an MI and compared to those without mental illness, patients with an SMI were less likely to receive coronary revascularisation procedures, less likely to survive 30-days post-MI and more likely to experience a further vascular event (36,37). The adverse cardiac and metabolic side effects of some antipsychotic medications may also play a role in the poorer outcomes (38,39).…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, optimal monitoring may not translate into optimal treatment of cardiovascular risk factors and/or established CVD. Furthermore, previous studies of general populations of people with and without diabetes have demonstrated suboptimal cardiovascular risk management in those with SMI (34,36). The excess risk of cardiovascular death in people with diabetes and SMI might also reflect more severe cardiovascular events and potential differences in cardiac care both in the acute phase and subsequently.…”
Section: Discussionmentioning
confidence: 96%
“…Factors contributing to excess mortality in people with mental disorders are multifold and intertwined, 9 , 10 and hence adoption of multilevel prevention and intervention framework managing risk factors at the individual, health-system and socio-environmental levels is warranted to achieve health outcomes improvement. 136 Individual-level strategies targeting people with mental disorders include optimising management of mental disorders, early detection and equitable treatment of physical morbidity, 16 , 137 lifestyle interventions addressing modifiable risk factors, such as regular exercise, smoking cessation and weight reduction. 138 Health system-focused interventions implemented within healthcare services comprise regular, guideline-concordant monitoring of medication-induced metabolic side-effects, 139 and facilitation of coordinated psychiatric and physical healthcare delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The association between SMI and increased risk of major cardiovascular disease events such as heart attack and stroke is well established (4)(5)(6). Pre-existing SMI is associated with lower short-and long-term survival following these events (6)(7)(8), as well as higher risks of recurrent vascular events (9). Sub-optimal clinical care for CVD may play a role in these disparities (6), including under-treatment with guideline-recommended medication for cardiovascular risk factors or established disease (7,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%